(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Prejudices against women in Africa are culturally deep-rooted. Cultural practices in Africa have consistently impinged on the dignity and rights of women in Africa. This paper explores some of the practices presented in Lonely Days by Bayo Adebowale that impinged on the dignity and rights of women in Africa. Some of the practices that make life worst for the widows in Africa are: false accusation, cap-picking ceremony and widows’ path. These practices worsen the condition of widows who deserve compassion not cruel treatment. The paper quotes different instances of widows’ suffering caused by cultural practices from the text where Kufi village is used to symbolize Africa. The paper recommends among other things: cultural practices should be ignored as they are contradictory and widows deserve to be taken care of cpnsidering the life they going into.